Tujuan dan Materi Pembelajaran Bahasa dan Sastra Indonesia - Ihwan, Ihwan; Fadlurrahman, Muhammad; Siahaan, Sevinna; Wabdaron, Densemina Yunita (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is a literature study that aims to examine in depth the relationship between the goals and learning materials of Indonesian Language and Literature in the context of 21st century education. This study is based on systemic functional linguistic theory, communicative theory, and constructivist approaches in language learning. Indonesian Language and Literature learning is seen not only as a means of mastering language skills, but also as a medium for personality development, critical thinking, and character formation of students. The results of the study show that the learning objectives of Indonesian Language and Literature include cognitive, affective, and psychomotor dimensions that are oriented towards the development of communicative and appreciative competencies. Learning materials, on the other hand, function as a concrete representation of these goals, including listening, speaking, reading, writing, and appreciating literary works based on social and cultural contexts. Text-based learning and project-based learning have proven to be useful for improving students' literacy, critical thinking skills, and students' creative ability to understand language and literature as a whole. According to this study, the relationship between learning materials and objectives is integrative and functional. The goal shows how learning can be achieved, while the material helps to achieve it through meaningful learning experiences. Therefore, in the process of learning Indonesian language and literature, contextual, humanistic, and literary aspects must be emphasized so that students can not only use the language well, but also become sensitive to society and appreciate the human values contained in literary works.